A Single-institution Comparison of Cetuximab, Carboplatin, and Paclitaxel Induction Chemotherapy Followed by Chemoradiation (CRT) Versus CRT for Locally Advanced Squamous Cell Carcinoma of the Head and Neck (LA-SCCHN). (October 2016) - Grover, Surbhi; Mitra, Nandita; Wan, Fei; Lukens, John N.; Sharma, Sonam; Bauman, Jessica; Masroor, Farzad; Cohen, Roger B.; Desai, Arati; Algazy, Kenneth; Alonso-Basanta, Michelle; Ahn, Peter; et al.
Abstract : Objectives: Comparisons of induction chemotherapy (IC) against upfront chemoradiation (CRT) for locally advanced head and neck cancer (LA-HNSCC) have demonstrated no differences except greater toxicity with IC. Effective induction regimens that are less toxic are therefore warranted. To inform future efforts with IC, we present our institutional experience comparing a less toxic IC regimen to CRT. Methods: We included patients with LA-HNSCC treated with organ-preservation CRT (+/−induction) between 2008 and 2011. Patients were of age above 18 years, ECOG performance status 0-1, and had minimum 6 months follow-up. IC consisted of 8 weekly cycles of cetuximab, carboplatin, and paclitaxel followed by CRT. The CRT regimen was platinum based, with cetuximab reserved for patients contraindicated to receive platinum. Results: Of 118 patients, 24 (20%) received IC and 94 (80%) received CRT. Median follow-up was 17 (IC) and 19 (CRT) months ( P =0.05). There were no differences in toxicity between the groups. IC patients were more likely male, with more advanced tumor and nodal stage. Even when controlling for these factors, IC was still associated with worse locoregional control (HR=3.6, P =0.02), distant metastasis–free survival (HR=5.3, P =0.02), and overall survival (HR=5.1, P <0.01). Conclusions: IC patients had greater disease burden than those receiving CRT. IC was well tolerated, but with significant rates of locoregional and systemic failures. Given the retrospective nature of the study, our findings are not meant to be definitive or conclusive, but rather suggestive in directing future efforts with IC. For now, we favor CRT as the standard option for treatment of inoperable LA-HNSCC.